DENSITY CHALLENGES OF HIGH-RISE RESIDENTIAL DEVELOPMENT IN MALAYSIA - Husin, Mohd Zamri; M. S. Usman, Ismar; Suratman, Robiah (PLANNING MALAYSIA, 2021)
Although the term ‘urbanisation’ was first coined in the 19th century, the phenomenon experienced a significant impact and received a lot of attention in the 21st century. One of the major results is density, causing effects such as excessive demand for residential buildings. To cope with the increasing urban population and limited land availability, cities can no longer opt for horizontal development strategies. Going vertical seems a practical solution, but it can lead to convoluted problems if it is not done with proper planning and mitigation measures at the preliminary stages of planning. This article describes the challenges of residential planning density for high-rise development in Malaysia using a systematic literature review on three identified real cases which separated by pre-development, post-development, and development control. The findings show the major challenges in pre-development and post development related to dissatisfaction with the increasing numbers of high-rise residences due to the increase in population and residential density. As a strategic development control, there must be uniformity in the act or law to control the development of this highrise residential. Thus, this article led to a better understanding of density related to high-rise residential development in Malaysia.